The effect of needle and syringe program on injecting drug users’ use of non-sterile syringe and needle behaviour in Palembang, South Sumatera Province, Indonesia - Najmah; Nuralam Fajar; Rico Januar Sitorus (Universiti Kebangsaan Malaysia, 2011)
HIV/AIDS has become one of international public health problem. An effective method to spread HIV/AIDS is through shared needle and syringe among Injecting Drug Users (IDUs). Many studies have been undertaken to know the effect of Needle and Syringe Program (NSP) to reduce the risk behaviours of IDUs in sharing needle and syringe among IDUs. NSP has been implemented in Palembang since 2009. However, there is no previous research to examine IDUs behaviours in using non sterile injection and syringe in Palembang.Therefore, a research is needed to be undertaken to know the effect of NSP on IDUs’ behaviours in using sterile needle an syringe.To identify association between seeking behaviours of NSP on IDUs’ behaviours in using sterile needle and syringe.This was a case control study with respondents recruited using snowball and purposive technique. Simple and multiple logistic regression tests were performed using statistics program (Stata version 10) to identify main association between NSP access status and behaviours of using non-sterile needle and syringe. Some possible confounders were also explored. Odds ratio, 95 % Confidence interval and P value were reported.There were 121 IDUs, consisting of 41 IDUs in cases group (High risk group to use non sterile injection and syringe) and 80 IDUs in control group (low risk group to use non sterile injection and syringe). Mostly, respondents were male with senior high school education level and single status. Crude odds ratio indicated that IDUs accessing NPSs had an odds of 1.07 to share needle and syringe among IDUs compared to IDUS without accessing NSPs (OR=1.07, 95 % CI = 0.49-2.31), p=0.87). After OR was adjusted by knowledge about the spread and prevention of HIV/AIDS, IDUs’ Attitude towards Harm Reduction, education level, age, length of using Injectig, and income level, IDUs accessing NSPS tend to minimize their behaviours to share needle and syringe compared to IDUs in NSPs group by 29 % (odd ratio, 0.69, 95 % CI = 0.23-2.06, p=0.51). P value showed that there is weak evidence against the null hypotesis of no association between IDUs accessing NSPs and risk behavior of using non-sterile needle and syringe. Previous studies indicated that IDUS using NSPs tend to reduce the use of shared needle and syringe, and tend to wash their needle and syringe before another IDUs use them again (Gibson, 2001, Wodak A & Cooney A 2006). Therefore, NSP increase awareness of IDUs to prevent the spread of HIV/AIDS.Availability of NSP appeared to reduce the use of shared or non-sterile syringe or needle in this study, although the association was not significant. One of the reasons could be the free access of needle and syringe in pharmacy could be one confounding factors that contributed to this non significant association. Further research with bigger sample size and qualitative research to explore more in-depth information about IDUs’ behaviours in using non-sterile injection and syringe is recommended.